HUBUNGAN BODY IMAGE DENGAN SELF-ACCEPTANCE (PENERIMAAN DIRI) PADA PASIEN ULKUS DIABETIKUM DI RUMAH SAKIT TK II PUTRI HIJAU KOTA MEDAN TAHUN 2016 - Kristina L Silalahi (Jurnal Keperawatan Priority, 2018)
Diabetic ulcers is one chronic complication of DM that is mostly feared. Diabetic ulcer complications in patients with DM may can affect their body image. Body image is a collection of individual attitudes either consciously and unconsciously of the body, including the perception of past and present, as well as a sense of structure, form, and body functions. Patients with diabetic ulcers require good self-acceptance that can run theri life normally. The objective of this study is to find out relationship between body image and self acceptance on diabetic ulcus patients in Putri Hijau Hospital medan in 2016. This is a survey analytic reseach with cross-sectional design. The study populations were 45 respondents and 16 respondents were taken to be the samples using saturated sampling technique. Data were proceeded and analysed using Chi-square with fisher’s exact test. Based on the result of the study, it is found that there is a relationship between body image and self acceptance on diabetic ulcus patients in Putri Hijau hospital in 2016 with the significance level of (α) = 0,05 and df=1 in which the calculation of p value was 0.018. The study concludes that there is a relationship between body image and self acceptance on diabetic ulcus patients. Medical personnels should give information and motivation to patients of diabetic mellitus especially for those suffering from diabetic ulcus disease.